Malignancy and Mortality in Idiopathic Inflammatory Myositis: A Retrospective Single-Center Cohort Study - Ulutaş, Firdevs; Çobankara, Veli (The European Research Journal, 2026)
Objectives: Idiopathic inflammatory myositis (IIMs) comprise a heterogeneous group of rare autoimmune muscle diseases characterized by variable clinical presentations and outcomes. While infections are a common cause of early mortality, malignancy has been recognized as the predominant driver of late mortality. This study aimed to evaluate malignancy frequency, mortality, and associated factors in a single-center IIM cohort. Methods: In this retrospective cohort study, all patients diagnosed with IIM and followed at Pamukkale University Faculty of Medicine between 2010 and 2025 were analyzed. Mortality rates, malignancy prevalence, and potential demographic and clinical determinants were assessed. Multivariable logistic regression analyses were performed, and results were reported as odds ratios with 95% confidence intervals. A two-sided P-value <0.05 was considered statistically significant. Results: A total of 66 patients were included, nearly three-quarters of whom were female. Concomitant malignancy was identified in 8 (12.1%) patients, and 10 (15.2%) patients died during the follow-up period. Mortality was substantially higher among patients with malignancy compared with those without cancer (50.0% vs. 10.3%). When survivors were compared with deceased patients, the latter exhibited a significantly greater comorbidity burden and a higher prevalence of malignancy. The comorbidity burden did not reach statistical significance in multivariable analyses. Kaplan–Meier survival analysis demonstrated significantly reduced overall survival in patients with concomitant malignancy compared with those without malignancy (log-rank P=0.014). Conclusions: The prevalence of malignancy in this cohort was consistent with previously published data, supporting the external validity of our findings. Mortality was markedly higher among patients with cancer, and malignancy was disproportionately represented among deceased individuals. Survival analyses further underscored malignancy as a major determinant of poor outcomes in patients with IIMs.